2019
DOI: 10.24246/j.js.2019.v9.i3.p217-226
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Rasa Percaya Diri Terhadap Motivasi Berprestasi Siswa pada Mata Pelajaran IPA

Abstract: This research aims to examine whether there is an influence of self-confidence in students' motivation to achievement in science lesson in elementary schools. This is a field research, where the researchers are involved directly down to the place of research to collect the data relevant to the indicators in the research objectives, which classifies this as a field research with a correlational quantitative approach. Correlational quantitative research is research to determine the level of relations between two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 21 publications
0
13
1
17
Order By: Relevance
“…Students' creativity will not occur if teacher is too fixated with curriculum administration affair, and there is unsupportive learning environment (Beetlestone, 2013;Runco et al, 2017;Yang et al, 2016), while confidence is formed through the process of practice and learning. Confident will encourage action that is more convincing and full of responsible in re-doing the action that had been learnt (Asiyah et al, 2019;Liu et al, 2019). Confidence also develops in collaborative learning process (Nurhayati et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students' creativity will not occur if teacher is too fixated with curriculum administration affair, and there is unsupportive learning environment (Beetlestone, 2013;Runco et al, 2017;Yang et al, 2016), while confidence is formed through the process of practice and learning. Confident will encourage action that is more convincing and full of responsible in re-doing the action that had been learnt (Asiyah et al, 2019;Liu et al, 2019). Confidence also develops in collaborative learning process (Nurhayati et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of our study were supported by other studies which showed a relationship between selfconfidence and motivation. For instance, in 2019, Aisyah concluded that if students had a high level selfconfidence, they also had a high level of motivation to excel [7]. Another study conducted by Wijaya (2018) also showed that there was a relationship between the level of self-confidence and motivation in badminton athletes statistically [8].…”
Section: Discussionmentioning
confidence: 99%
“…Majunya suatu bangsa dipengaruhi oleh mutu pendidikan dari bangsa itu sendiri karena pendidikan yang tinggi dapat mencetak sumber daya manusia yang berkualitas (Walid, 2017). Pendidikan yang dimaksud bukan bersifat informal melainkan bersifat formal meliputi proses belajar mengajar yang melibatkan guru dan siswa (Asiyah et al, 2019). Pendidikan pada hakekatnya merupakan syarat mutlak bagi pengembangan sumber daya manusia dalam menuju masa depan yang lebih baik.…”
Section: Pendahuluanunclassified